If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + -8) = 3x + -24 Reorder the terms: 6(-8 + x) = 3x + -24 (-8 * 6 + x * 6) = 3x + -24 (-48 + 6x) = 3x + -24 Reorder the terms: -48 + 6x = -24 + 3x Solving -48 + 6x = -24 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -48 + 6x + -3x = -24 + 3x + -3x Combine like terms: 6x + -3x = 3x -48 + 3x = -24 + 3x + -3x Combine like terms: 3x + -3x = 0 -48 + 3x = -24 + 0 -48 + 3x = -24 Add '48' to each side of the equation. -48 + 48 + 3x = -24 + 48 Combine like terms: -48 + 48 = 0 0 + 3x = -24 + 48 3x = -24 + 48 Combine like terms: -24 + 48 = 24 3x = 24 Divide each side by '3'. x = 8 Simplifying x = 8
| -3sinx+6cosx=0 | | -4u+5=-7(u-2) | | 3x/9=3 | | 15/x=4-1/x | | 12x-4.9x^2=0 | | 1/4=8/y | | 12/18=2/w | | 2x+5x^2=1 | | T=(y+sw)(1+d) | | 24x^2-82x=-33 | | 20=-9+8(c-7) | | 3m-m=5-4+2m+5-5m | | y=10x^2-x-3 | | 10/b=60/12 | | 3s-5s=34 | | -5+9b+7= | | 9.7+3.1w-1.9forw=2.3 | | c^2-c-20=0 | | 2k-5+k-3=2+2k+5 | | 6x^-2/3*9x^-4*x^3 | | y=-6x+32 | | 3x-5+2x+1=21 | | 1x-4=-5x-28 | | 3(7-5p)=0 | | 5(3x+2)=-15 | | 3x-5/2=-8 | | 0=t^2-3t^2-4t | | 4/7x7/11 | | -30=-9n+5n | | -30=-9n | | y=5x^2-4x | | 6(5v-8)=-25-4v |